2008
DOI: 10.3748/wjg.14.1060
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-regulation of lower esophageal sphincter Predictive value of Ki67 and p53 in locally advanced rectal cancer: Correlation with thymidylate synthase and histopathological tumor regression after neoadjuvant 5-FU-based chemoradiotherapy

Abstract: AIM:To investigate the predictive value of Ki67 and p53 and their correlation with thymidylate synthase (TS) gene expression in a rectal cancer patient cohort treated according to a standardized recommended neoadjuvant treatment regimen. METHODS:Formalin fixed, paraffin embedded pretherapeutical tumor biopsies (n = 22) and posttherapeutical resection specimens (n = 40) from patients with rectal adenocarcinoma (clinical UICC stage Ⅱ/Ⅲ) receiving standardized neoadjuvant 5-fluorouracil (5-FU) based chemoradiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 34 publications
(28 reference statements)
3
56
0
3
Order By: Relevance
“…A significant correlation was observed of Ki-67 labeling index and RTA (P \ .0001) in agreement with the results by Jacob et al [29]. It appears plausible that the persistence of a fraction of high-proliferative cells in a larger RTA might be representative of resistant clones of cells and therefore, of a more aggressive phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…A significant correlation was observed of Ki-67 labeling index and RTA (P \ .0001) in agreement with the results by Jacob et al [29]. It appears plausible that the persistence of a fraction of high-proliferative cells in a larger RTA might be representative of resistant clones of cells and therefore, of a more aggressive phenotype.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, high levels of TS are often associated with a high proliferating pattern (i.e. extensive Ki67 staining) [44,45]. Because highly proliferating tumors may be more susceptible to chemotherapy [46] and chemoradiotherapy [24], the positive predictive role of TS and Ki67 in our analysis might reflect a good response to a very active chemotherapy regimen by highly proliferating rectal tumors.…”
Section: Discussionmentioning
confidence: 89%
“…The inclusion of p21 screening is warranted, as the referenced studies in (Salonga, Danenberg et al 2000), (Lenz, Danenberg et al 1998). Numerous studies assessing TS expression have found that pretreatment biopsies negative for TS were predictive of response (Saw, Morgan et al 2003), (Diez, Ramos et al 2003), (Jakob, Liersch et al 2008), (Negri, Campanini et al 2008). 3 studies revealed a better outcome with low or absent pretreatment TYMS expression, however another study demonstrated better outcome with high TYMS expression.…”
Section: P21mentioning
confidence: 99%
“…While it has been used as a prognostic factor for colorectal cancer, results have been inconclusive (Ogata, Greca et al), (Guzinska-Ustymowicz, Pryczynicz et al 2009), (Santagostino, Saggia et al 2007). A small number of independent studies have examined the levels of Ki67 positivity in pretreatment biopsies from rectal cancer patients (Kudrimoti, Lee et al 2007), (Debucquoy, Goethals et al 2006), (Tannapfel, Nusslein et al 1998), (Reerink, Karrenbeld et al 2004), (Rodel, Grabenbauer et al 2002), (Charara, Edmonston et al 2004), Some studies have shown a positive association with Ki67 index higher in responders compared to non responders (Kim, Park et al 2001;Jakob, Liersch et al 2008). The remaining studies showed no correlation between Ki67 status and patient outcome.…”
Section: Ki67 and Cox2mentioning
confidence: 99%